Synthetic biology approaches for biotechnology applications (Abordagens de Biologia Sintética para Aplicações na Biotecnologia) - Rodrigues, Joana Lúcia Lima Correia (2023)
In this invited lecture, Synthetic Biology is presented as a powerful technology to solve many problems in different fields. After discussing the most important synthetic biology tools, applications in several industries (chemical, food, pharmaceutical), environment, and health (vector control and treatment) were presented.